The Existence of Traditional Markets Post-Regional Autonomy in Bukittinggi, West Sumatra - Kahanna, Mutia; Rahmi , Hijratur; Mardhatillah , Muntaha (Kirana Publisher (KNPub), 2025)
The research reviewed the existence of traditional markets after regional autonomy in the context of modern market development in Bukittinggi. Using qualitative methods, data were collected through observation, direct interviews, and documentation. Market theory and functional structure theory were employed to analyze the data. The results demonstrate the importance of traditional markets for fulfilling the community’s needs. The traditional markets in Bukittinggi consist of Pasar Atas, Pasar Aur Kuning, and Pasar Bawah. Marketers undertake various efforts to survive, such as managing their goods, modifying approaches, prioritizing quality and freshness, building good relationships with buyers, and promoting through social media. The government also takes responsibility for maintaining the existence of traditional markets by providing grants for COVID-19-affected sellers, assisting fire victims, reducing sellers' retribution, and revitalizing traditional markets.